Imaging Gene Expression Methods and Protocols - Shav-Tal, Yaron; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
As imaging technologies and approaches have evolved, the scope of certain imaging techniques has moved far beyond the production of purely illustrative images or appealing time-lapse movies to providing the scientist with a rich range of ways to measure and quantify the biological process and outcome of gene expression.  In Imaging Gene Expression: Methods and Protocols, expert authors offer up-to-date approaches and protocols that scientists in the field have developed, which would benefit the broader scientific community. Divided in three convenient parts, this detailed book covers the output of a gene, namely the RNA molecules that are transcribed from the gene and the way by which these molecules can be tracked or quantified in fixed or living cells, protocols that focus on the gene, DNA, or chromatin, as well as a variety of ways by which nuclear processes intertwined with gene expression can be followed and quantified in living cells as well as approaches for studying several sub-nuclear structures found in eukaryotic cells.  Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective subjects, lists of materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Authoritative and up-to-date, Imaging Gene Expression: Methods and Protocols will serve researchers working toward imaging in the context of complete organisms.
High-Throughput Fluorescence-Based Screen to Identify Factors Involved in Nuclear Receptor Recruitment to Response Elements -- Live-Cell Imaging Combined with Immunofluorescence, RNA, or DNA FISH to Study the Nuclear Dynamics and Expression of the X-Inactivation Center -- Single Molecule Resolution Fluorescent In Situ Hybridization (smFISH) in the Yeast S. cerevisiae -- Measuring Transcription Dynamics in Living Cells Using Fluctuation Analysis Nuclear Poly(A) RNA Movement Within and Among Speckle Nuclear Bodies and the Surrounding Nucleoplasm -- Nuclear Trafficking and Export of Single, Native mRNPs in Chironomus tentans Salivary Gland Cells -- Single mRNP Tracking in Living Mammalian Cells -- Imaging Nascent RNA Dynamics in Dictyostelium -- Monitoring Dynamic Binding of Chromatin Proteins In Vivo by Single Molecule Tracking -- Single Particle Tracking for Studying the Dynamic Properties of Genomic Regions in Live Cells -- Microscopic Analysis of Chromatin Localization and Dynamics in C. elegans -- Measuring the Dynamics of Chromatin Proteins During Differentiation -- Electron Spectroscopic Tomography of Specific Chromatin Domains -- BAC Manipulations for Making BAC Transgene Arrays -- Spatio-Temporal Visualization of DNA Replication Dynamics -- The Dynamics of DNA Damage Repair and Transcription -- Fluorescence Microscopy-Based High-Throughput Screening for Factors Involved in Gene Silencing -- Actin as a Model for the Study of Nucleocytoplasmic Shuttling and Nuclear Dynamics.- Isochronal Visualization of Transcription and Proteasomal Proteolysis in Cell Culture or in the Model Organism, Caenorhabditis elegan -- Considering Discrete Protein Pools When Measuring the Dynamics of Nuclear Membrane Proteins -- Correlative Microscopy of Individual Cells: Sequential Application of Microscopic Systems with Increasing Resolution to Study the Nuclear Landscape -- Time-Lapse, Photo-Activation, and Photo-Bleaching Imaging of Nucleolar Assembly after Mitosis -- Nucleation of Nuclear Bodies.
Keywords: Radiology; Gene expression; Imaging / Radiology; Gene Expression